Avaliação microestrutural e propriedades de cascas cerâmicas contendo diferentes tamanhos e concentrações de nanopartículas de sílica coloidal - Iona Macedo Leonardo Machado (2013)
Parts having excellent surface finishing and low dimensional tolerances characterize the investment casting. These characteristics are related to wax properties of copying details and reproducing the details by ceramic shells. The objective of this study was to evaluate the effects of varying the size and concentration of colloidal silica nanoparticles in the properties of ceramic shells and evaluate the microstructures. Three types of backup slurries were evaluated with colloidal silica sizes of 13nm, 8nm, and 5nm. A fourth type showing distribution of sizes of 14nm to 22nm was also investigated. Slurries prepared with silica binders of 8nm and 13nm were evaluated at concentrations of 15%, 20%, 25%, and 30%. The slurry prepared with silica binder of 5nm was evaluated at 15% and 10% and the slurry prepared with silica binder of 14nm to 22nm was evaluated at concentrations of 40%, 30% and 15%. Several processing parameters were controlled. Flexural strength and permeability were evaluated. The atomic force microscopy was used to characterize the different sizes of colloidal silica. Microstructural characterization of ceramic shells was performed by pycnometry, scanning electron microscopy, and X-ray computed microtomography (-CT). For the studied conditions the maximum flexural strength was observed for ceramic shell with silica binder of 8nm. The ceramic shell with silica binder of 8nm showed higher strength at lower silica concentrations than ceramic shell with silica binder of 13nm. For the same concentration of silica, the flexural strength for shells with silica binder of 5nm is close to those obtained for the ceramic shells with silica binder of 13nm. The results of flexural strength for ceramic shells with silica binder of 14nm to 22nm and 30% of colloidal silica are close to the values for the shell with silica binder of 13nm. In general the curve of permeability showed an inverse behavior to the flexural strength curve. Picnometry showed that the bulk density is lower than the apparent density. Microstructural differences between green and fired shells were observed by scanning electron microscopy and X-ray computed microtomography. Fractures of the shells showed that stucco grains of fired ceramic shells were much more apparent than stucco grains of green shells. This behavior is typical for stronger material. We observe through the microtomography that porosity and average pore diameter of shells decreased after firing.